THE PROBLEMS OF WAR AND PEACE ON THE PAGES OF «VESTNIK EVROPY» («HERALD OF EUROPE») MAGAZINE, 1898-1899 (BASED ON THE MATERIALS OF L. Z. SLONIMSKY) - Nikolay Nikolaev (Гуманитарные и юридические исследования)
The article deals with the analysis of the key authors' views of the Herald of Europe Magazine on the Hague Peace Conference of 1899 which became an important event in the international law and favored the public peacemaking mood development. Besides, the performed analysis brings out the viewpoint of the editorial staff on the most important social and political problems discussed on Russian peace initiative. The problems, which were raised on the pages of the magazine from autumn/summer season 1898-1899, included such topics as the struggle against militarism, the everlasting peace achievement, the armament and military budget limitation, the humanitarian law codification and the arbitration formation. The paper shows a good reaction of «the Herald of Europe Magazine» toward the Russian government proposal to convene a peace conference, observes restrained optimism toward its possible results and states positive attitude to the results. The conclusion made in the article is following: the position of the magazine was dictated first of all by its liberal ideology oriented to «state pacifism» and peaceful foreign policy which is very important for implementing burning domestic reforms.